The presence and the anatomical variations of the accessory appendicular artery: A systematic review of 604 cases - Savvakis, Stavros; Karamitsou, Paraskevi; Vardaxi, Chrysoula; Forozidou, Evropi; Emfietzis, Panagiotis Konstantinos; Mantsopoulos, Konstantinos; Anastasopoulos, Athanasios; Poutoglidis, Alexandros (Anz Journal of Surgery, 2024)
Introduction: The accessory appendicular artery (AAA) is an accessory source of blood supply to the appendix. Its existence and potential point of origin are seldom addressed in the literature. Methods: To fill this knowledge gap, we performed a systematic review of all available studies involving both cadaveric and surgical specimens and documented the presence and the origin of the AAA, following the guidelines outlined in the preferred reporting items for systematic reviews and meta-analysis (PRISMA) statement. Results: Eleven studies, with an overall of 604 specimens were included. Our research revealed that the AAA is notably absent in most cases (83.6%). When present, it most commonly originates from the posterior cecal artery (12.4%), followed by the descending branch of the ileocolic artery (2%), and the ileal branch of the ileocolic artery (0.7%). Instances of origin from the anterior cecal, common cecal, or the ileocolic trunk were even more infrequent. Based on our observations, we introduced a new simplified classification system. Discussion: The effect of an accessory artery on the process of appendicitis remains to be clarified. We firmly recommend that surgeons should consider the possible presence and various origins of the AAA during appendectomy procedures to avoid serious complications.
CRIS-Team Scopus Importer:2024-05-31
Keywords: accessory; anatomy; appendicular artery; appendicular artery; appendix; cadaveric; dissection